2007
DOI: 10.2220/biomedres.28.287
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum cholinesterase level and urinary bladder activity in patients with or without overactive bladder and/or neurogenic bladder

Abstract: We compared the serum cholinesterase (ChE) level and various parameters between patients with or without overactive bladder (OAB) and/or neurogenic bladder (NB). A total of 258 patients who met the following criteria were enrolled: the presence/absence of OAB and/or NB was documented, laboratory data were available, and liver and renal functions were normal. Patients were divided into the 3 groups: 1) a NB /OAB + group, a higher serum albumin or ChE level was associated with a better therapeutic outcome. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Whether this mechanism is present in the normal human bladder and whether it is enhanced in overactive bladder would be of great interest. Recently, it has been shown that a decrease of serum cholinesterase is related to occurrence of overactive bladder (Sugaya et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Whether this mechanism is present in the normal human bladder and whether it is enhanced in overactive bladder would be of great interest. Recently, it has been shown that a decrease of serum cholinesterase is related to occurrence of overactive bladder (Sugaya et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although reversible cholinesterase inhibitors are beneficial for the treatment of Alzheimer's disease [4][5][6], myasthenia gravis [7], and neurogenic bladder [8,9], they can still cause adverse cholinergic reactions. Excessive cholinesterase inhibition can cause cholinergic crisis, defined by symptoms including pupils ≤ 2 mm in diameter, fasciculations, heart rate ≤ 60 beats per minute, systolic blood pressure ≤ 80 mmHg, decreased consciousness (Glasgow Coma Scale < 15), excessive sweating, or poor air entry due to bronchorrhea and/or bronchospasm [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This condition has been reported to result in delayed removal of the large acetylcholine burst secreted by the parasympathetic nerve terminals in the bladder when the micturition reflex is activated [20]. Sugaya et al also reported a significant association between the serum levels of cholinesterase and albumin [21]. The presence of a cholinergic effect will cause a bladder spasm, resulting in frequency and urgency.…”
Section: Discussionmentioning
confidence: 99%